Adaptive characteristics of the gut microbiota of the scaly-sided merganser (Mergus squamatus) in energy compensation at different developmental stages - Yu, Yanze; Wang, Jiaming; Shi, Luyi; Sun, Hongyu; Cheng, Boxing; Sun, Yue (Frontiers in Microbiology, 2025)
The gut microbiota is crucial for maintaining health, enhancing digestive efficiency, and promoting the development of the immune system of the host. However, for the endangered waterfowl, the scaly-sided merganser (Mergus squamatus), the physiological role of the composition and structure of its gut microbiota during its growth and development remains unclear. Herein, we conducted fecal metagenomic analyses on adult and subadult populations to assess differences in the gut microbiota composition and function within the same habitat. The results revealed that this species harbors a diverse gut microbiota assemblage, with Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes being the dominant phyla in adults and subadults. Notably, the abundance of the Firmicutes phylum is higher in adult, while the Actinobacteria phylum is more abundant in subadult individuals. There are significant differences in the diversity of the gut microbiota between the two age groups of the scaly-sided merganser. The alpha diversity index shows that the species richness and evenness of gut microbiota in adult scaly-sided merganser are higher than those in subadult individuals. Functional gene enrichment analysis further indicated that the adult gut microbiota had a higher ability to synthesize acetyl-CoA and pyruvate, along with enhanced conversion of acetyl-CoA to acetate. These findings suggest that the gut microbiota of the scaly-sided merganser can play a crucial role in concert with the host during the energy metabolism process in the growth and development stage. This study provides foundational data on the gut microbiota structure and function of this species and enhances our understanding of microbial dynamics during waterfowl development.